A Pathological Study of the Epidemiology of Atherosclerosis in Mexico City. (26th February 2014) - Rodríguez-Saldaña, Joel; Rodriguez-Flores, Marcela; Cantú-Brito, Carlos; Aguirre-Garcia, Jesús
Abstract : Objective . To examine the frequency and patterns of association of cardiovascular risk factors with atherosclerosis in five different arterial territories at post-mortem in Mexico City. Methods . We obtained five arterial territories arteries (circle of Willis, coronary, carotid, renal, and aorta) of 185 men and women 0 to 90 years of age who underwent autopsy at the Medical Forensic Service of Mexico City. We determined the prevalence and extent of atherosclerotic lesions by histopathology according to the classification of the American Heart Association as early (types I–III) and advanced (types IV–VI), and according to the degree of stenosis and correlated with cardiovascular risk factors. Results . Atherosclerotic lesions were identified in at least one arterial territory in 181 subjects (97.8%), with involvement of two ore more territories in 178 subjects (92.2%). Advanced lesions were observed in 36% and 67% of subjects under 15 and between 16 and 35 years, respectively. Any degree of atherosclerosis was associated with the presence of diabetes mellitus, hypertension, overweight, obesity, and smoking, and to a greater extent with the presence of two or more risk factors (P < 0.001 ). However, emerging and advanced athersoclerosis was observed in 53% and 20% people with no risk factors. Conclusions . The study shows a high prevalence of atherosclerosis in all age groups and both sexes. There is considerable development of atherosclerotic disease in subjects without known risk factors.